Industrial growth in a primary export model and in a import substitution model: the Peruvian case, 1958-1969 - De la Cuba, Mauricio (1988)
This article analyzes the evolution of the industrial sector in Peru in 1985-1969. In the first period, 1958-1963, characterized by the application of a political economy that limited the domestic demand expansion and favoured an extraordinary increase of exports, the most dynamic industrial activities were related to the transformation of primary products (metals and flashmeal) and incentivated a sustitutive process in some other activities. In the second period, 1963-1969, exports stagnated, the expansion of domestic demand and a great a-tariff protection induced a pattern of industrial growth quite different to the preceeding period. Activities oriented to the domestic market, particularly those associated to import sustitution were stimulated.